Analisis Kelayakan Kapasitas Produksi Mesin Belt dengan Metode Rough Cut Capacity Planning (RCCP) pada PT YWN - Heriyono, Kintansari Hanifah Nur-Alfath; Wahyudin, Wahyudin; Azizah, Fahriza Nurul (Industrika : Jurnal Ilmiah Teknik Industri, 2025)
This study analyzes the feasibility of Belt machine production capacity at PT YWN using the Rough Cut Capacity Planning (RCCP) method with the Bill of Labor Approach (BoLA). This research was conducted because PT YWN faces obstacles in meeting demand due to imbalance in production capacity on the Belt machine. This condition can lead to increased lead time, non-optimal resource utilization, and increased production costs. Thus, this method is used to identify overloading or underloading of production capacity and improve the Master Production Schedule (MPS). The analyzed data includes production plan, process time, working time, and machine efficiency and utility. The results showed that work center 2 experienced a capacity shortage of -17%, thus requiring additional machines, while work center 4 experienced an overcapacity of 58%. Recommendations include MPS revision, subcontract, overtime, and machine addition. The conclusion of this research shows that the RCCP method with BoLA approach is effective in evaluating production capacity, improving efficiency, and overcoming capacity imbalance. The results of this study are expected to help PT YWN in managing production capacity more effectively and efficiently. Keywords : Bill of Labor Approach (BoLA), Production capacity, Productivity, Rough Cut Capacity Planning (RCCP)